Demand for "Healthy" Products: False Claims and FTC Regulation. (December 2017) - Rao, Anita; Wang, Emily
Firms sometimes make selective or deceptive claims, which can have negative consequences for consumers, especially if consumers are not fully informed and the claims are hard to verify. This study aims to measure the decline in demand that a firm making such claims faces when caught. In addition, it seeks to understand which type of consumer these claims primarily affect. Using a panel data set of consumer purchases and firm advertising, the authors measure this impact by exploiting the fact that four popular products settled charges raised by the Federal Trade Commission. They further control for and document firm responses in terms of price and advertisement changes around the date of the settlement. Findings indicate a significant decline in demand following the termination of the claims, resulting in a 12%–67% monthly loss in revenue across the four products, which amounts to a .40 million–3.82 million loss in monthly revenue. They also find that these claims primarily affect consumers who are newcomers.